Tubercular Lymphadenitis in Paediatric Patient in E.N.T. Practice - Chesti, M Lateef; Iqbal, Irfan; Showkat, Showkat A; Qazi, Sajad M; Rehman, Ayaz; Amin, Zarka (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Tuberculosis is one of the biggest health challenge, the world is facing. Cervical lymphadenitis is a common manifestation of mycobacterial infections encountered in otorhinolaryngologic practices. It may be the manifestation of a systemic tuberculous disease or a unique clinical entity localized to neck. It remains a diagnostic and therapeutic challenge because it minimizes other pathological processes and eyelids in consistent physical and lab findings. A high index of suspicion is needed for the diagnosis of mycobact cervical lymphadenitis and should be considered in the differential diagnosis of a cervical mass especially in endemic areas. Key words: Cervicofacial masses; lymphadenopathy FNAB; HPE; developmental malformations; cystic lesions. DOI: 10.3126/saarctb.v5i2.3074 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(2) 31-35